Peran Pengelola Prodi Akuntansi Menyiapkan Mahasiswa Menghadapi Artificial Intelligence (AI) Akuntansi - Kusuma, Marhaendra; Saputra, Beny Mahyudi; Kasim, Che Manisah Mohd; Soares, Jaime (TEMA, 2024)
Artificial Intelligence (AI) has entered all aspects of life, including in the field of accounting. Prospective accountants must be ready to face it, and universities must prepare for it. This study aims to test the role of accounting study programs in fostering students' self-confidence in facing accounting artificial intelligence (AI). Data from 840 accounting students of PTN-PTS throughout Indonesia. The results of the study show that the accounting study program implementation system has a positive effect on competence and self-confidence in working with AI. The accounting study program has been effective in fostering students' competence and self-confidence in facing AI. The originality of this study: 1) modifying the size of the curriculum variables by including character education indicators and expanding it to the study program implementation system, and 2) testing differences in student characteristics in their self-confidence in working with AI.   Abstrak Artificial Intelligence (AI) memasuki semua sendi kehidupan, termasuk bidang akuntansi. Calon akuntan harus siap menghadapinya, dan perguruan tinggi harus mempersiapkannya. Penelitian ini bertujuan menguji peran prodi akuntansi dalam menumbuhkan rasa percaya diri mahasiswa menghadapi artificial intelligence (AI) akuntansi.Data dari 840 mahasiswa akuntansi PTN-PTS se-Indonesia. Hasil penelitian menunjukkan bahwa sistem penyelenggaraan prodi akuntansi berpengaruh positif terhadap kompetensi dan kepercayaan diri bekerja dengan AI. Prodi akuntansi telah efektif dalam menumbuhkan kompetensi dan rasa percaya diri mahasiswa dalam menghadapi AI. Originalitas penelitian ini : 1) memodifikasi ukuran variabel kurikulum dengan memasukkan indikator pendidikan karakter dan memperluas ke sistem penyelenggaraan prodi, 2) menguji perbedaan karakteristik mahasiswa akan kepercayaan dirinya bekerja dengan AI.